Az Európai Unió további bővülése : a jugoszláv utódállamok - Lőrinczné Bencze, Edit (Közép-Európai Közlemények, 2010)
Enlargement has been at the heart of the EU’s development over several decades. The present enlargement agenda covers the countries of the Western Balkans and Turkey. These countries have been given the perspective of becoming EU members once they fulfil the necessary conditions. The main question for most countries from the Balkans has not been whetherbut when and under what conditions would be the next enlargement occurs. The Western-Balkans path towards the European Union is grounded within the Stabilization and Association Process developing as a framework to contribute to the longterm security and stability of the region. The EU bringing the Western Balkans closer to the European integration, introduced new type of association agreement with the EU, called the Stabilization and Association Agreement (SAA). It opens the possibility of individual progress towards a later stage of membership negotiations.